Manajemen Strategi Pengelolaan Kelas dalam Meningkatkan Kualitas Layanan Pendidikan: Studi Deskriptif Analisis di SD Negeri Sindangraja 3, SDN Gunung Kembang, dan SD Islam Al Azhar 18 Cianjur - Abdulah, Muhamad Kosim; Fauzi, Ikka Kartika Abbas; Sudrajat, Adjat (Universitas Nusantara PGRI Kediri, 2022)
This study aims to describe the planning, implementation, evaluation, constraints, and results of implementing classroom management strategies in improving the quality of educational services. This data was obtained through classroom teacher interviews, the results of which were supporting data from the main source and observations regarding classroom management. After collecting data, qualitative data analysis was carried out on the instrument. The results showed that the elementary school teachers studied had implemented the planning, implementation, and evaluation of classroom management strategies. Class management strategy constraints that occur can be overcome properly. The results of implementing the classroom management strategy can be seen from the improvement in the quality of student learning, teacher professionalism, and the school's physical environment.